Uma Proposta de Extensão de um Middleware de Aquisição de Contexto para Suporte a Crowdsensing com Privacidade - Gomes, Francisco A. A.; Rocha, Lincoln S.; Trinta, Fernando A. M. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2015: Anais Estendidos do XXI Simpósio Brasileiro de Sistemas Multimídia e Web, 2015)
Mobile devices such as smarthphones have become a common tool in our daily routine. Mobile Applications (a.k.a. apps) have increasingly demanded access to contextual information, such as environment and system data, as well as user profile. These apps adapt themselves according this context data in order to improve their services. Mobile Applications with this behavior are known as context-aware applications. Several software infrastructures have been created to help the development of mobile context-aware applications, but most of them do not store the historic of contextual information, once mobile devices are resource constrained (computing and memory capabilities). They are not built taking into account the privacy of contextual information either, due the fact that apps can expose contextual data, without user consent. This paper addresses this topic by extending an existing middleware platform called LoCCAM to store and process large volumes of contextual information generated from several mobile devices (crowdsensing); and the definition of privacy policies that avoid dissemination of unauthorized contextual information.